Evaluation of Enterprise ICT Advancement - Bolek, Cezary; Grudzińska-Kuna, Agnieszka; Papińska-Kacperek, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Implementation of information and communication technologies (ICT) and further their adoption and use in enterprise is complex and multi-dimensional process. However once applied, ICT can provide foundation for innovation and become a trigger for new processes and organizational changes. It seems that sophistication of ICT use increase enterprise attractiveness to potential partners and investors. Importance of ICT in running a business bags the question how to measure level of ICT advancement. As the authors have decided to employ composite index that can be synthetic form of enterprise ICT advancement measure as well as evaluation and comparison tool, selection of key sub-indicators forms the article main issue.